Over 19 W Single-Mode 1545 nm Er,Yb Codoped All-Fiber Laser - Jiadong Wu; Chunxiang Zhang; Jun Liu; Ting Zhao; Weichao Yao; Pinghua Tang; Le Zhang; Hao Chen (Advances in Condensed Matter Physics)
We report a high-power cladding-pumped Er,Yb codoped all-fiber laser with truly single transverse mode output. The fiber laser is designed to operate at 1545 nm by the use of a pair of fiber Bragg gratings (FBGs) to lock and narrow the output spectrum, which can be very useful in generating the eye-safe ~1650 nm laser emission through the Stimulated Raman Scattering (SRS) in silica fibers that is of interest in many applications. Two pieces of standard single-mode fibers are inserted into the laser cavity and output port to guarantee the truly single-mode output as well as good compatibility with other standard fiber components. We have obtained a maximum output power of 19.2 W at 1544.68 nm with a FWHM spectral width of 0.08 nm, corresponding to an average overall slope efficiency of 31.9% with respect to the launched pump power. This is, to the best of our knowledge, the highest output power reported from simple all-fiber single-mode Er,Yb codoped laser oscillator architecture.